Pedunculated nevus lipomatosus cutaneous superficialis of the scrotum successfully removed by excision - Shikhar Ganjoo; M PS Sawhney; Uma Sharma (Wolters Kluwer Medknow Publications, 2018)
Nevus lipomatosis cutaneous superficialis is a rare cutaneous condition characterised by mature adipocytic hamartoma in the dermis amongst and splitting the collagen bundles. It was first reported in 1924. The first case report from India was in the year 1994. There is only 1 previous case report of the nevus occurring in the scrotum. The following case is reported for its rarity both in incidence and also the site involved. The lesion is asymptomatic and needs no treatment usually but since the lesion occupied a large area of scrotum we went ahead and did an excision of the nevus.